CATS AND JAPANESE IDIOMATIC EXPRESSIONS RELATED TO CATS AND THEIR BACKGROUND - Rina Koike (International Journal of Literature and Language Studies, 2026)
Taking up cats, which have been kept as pets since ancient times in Japan, we study the origin of the name